Ultra‐Sensitive and Highly Stretchable Strain Sensors for Monitoring of Human Physiology. Issue 3 (9th November 2021) - Verma, Ravi Prakash; Sahu, Prateekshya Suman; Rathod, Mitesh; Mohapatra, Soumya Sanjeeb; Lee, Junghoon; Saha, Biswajit
Abstract: The flexible strain sensors have potential applications in advanced electronics, health monitoring systems, wearable sensors, robotics, and human–machine interfaces. The development of highly sensitive, stretchable, and durable strain sensors is a challenging task for researchers. However, the sensors with a detection range from large strain to minute deflection are imperative for human‐interactive applications. This work has demonstrated a facile method of sensor fabrication, which use reduced graphene oxide (rGO) as sensing material and silicone sealant as a flexible substrate. Few‐layer rGO is synthesized by electrochemical exfoliation of pencil lead. The fabricated sensors have a gauge factor higher than 4000 and durability longer than 1600 cycles at 100% strain. At the same time, developed strain sensors exhibit detection capability over a wide range of strain (0–120%), which is an essential requirement of wearable sensors. To the best of the authors' knowledge, fewer works have reported strain sensors that have ultra‐high gauge factor (≥4000) in combination with high stretchability (>100%). Utilizing the ultra‐sensitivity and sub‐second response time of the rGO‐sealants, these wearable sensors are used to monitor physical activities, heartbeats, and finger touches. Abstract : Fabricated sensors have a gauge factor higher than 4000 and durability longer than 1600 cycles at 100% strain. The strain sensors exhibit detection capability over a wide range of strain (0–120%), which is an essential requirement of wearable sensors. Utilizing the ultrasensitivity and sub‐second response time, these sensors are used to monitor physical activities, physiological signals, and finger touch.